Удосконалення технології жувальної карамелі спеціального призначення - Божок, Олександр Сергійович (My University, 2017)
Робота присвячена розробці інноваційної технології жувальної карамелі для надання їй функціональних, дієтичних і дієтично-функціональних властивостей шляхом раціонального використання цукрів: сахарози, глюкози, фруктози, тагатози; цукрозамінників і ФФСІ. Досліджено можливість раціонального використання сахарози та глюкози у виробництві жувальної карамелі функціонального призначення та додання фізіологічно-функціональних сировинних інгредієнтів (пребіотика лактулози, аскорбінової кислоти, борошна зародків пшениці, харчової добавки “Гемовітал”). Встановлена і науково обгрунтована необхідність при виробництві жувальної карамелі дієтично-функціонального призначення використовувати суміш фруктоза- ізомальтитол та суміш тагатоза- мальтитол. Визначено вплив сировинних інгредієнтів на органолептичні, структурно-механічні показники жувальної карамельної маси. Визначено вплив сировини на сорбційно-десорбційні властивості жувальної карамелі та жувальний ефект. Диссертационная работа посвящена разработке инновационной технологии жевательной карамели специального назначения с функциональными и диетически- функциональными свойствами. The paper is devoted to the development of technology of chewing caramel to add functional, dietary and dietary and functional characteristics to chewing caramel through the rational use of sugars: saccharose, glucose, tagatose; sugar substitutes and Physiologically Functional Raw Ingredients which provide chewing caramel with the status ‘Functional Food Product’ and ‘Dietary and Functional Food Product’. The possibility of rational use of saccharose and glucose during the production of chewing caramel of functional use through the rational use of physiologically functional raw ingredients (prebiotic lactulose, ascorbic acid, flour of wheat germs, food adittive ‘Gemovital’) has been examined. The possibility of rational use of sugars of fructose, tagatose and new generation of sugar substitutes isomaltitol, maltitol during the production of chewing caramel having the status ‘Dietary and Functional Food Product’ has been confirmed. The technology of chewing caramel of functional and dietary and functional use as a complex thechnological system has been examined, the criteria of operation efficiency of the complex system and options to optimize individual subsystems have been identified. The technology of chewing caramel which is formed by casting method has been developed. Regulatory documentation on the chewing caramel of special use has been developed. The technologies tested in operating conditions and defended with Ukrainian patents have been updated.
Keywords: жувальна карамель; сахароза; глюкоза; лактулоза; фруктоза; тагатоза; chewing caramel; saccharose; glucose; lactulose; fructose; tagatose; кафедра технології хлібопекарських і кондитерських виробів